2019
DOI: 10.3390/w11112386
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Pressurized Rainfall Simulator for Evaluating Performance of Erosion Control Practices

Abstract: Construction site erosion and resulting sedimentation constitutes one of the greatest non-point source pollution threats to our nation’s waterways. Erosion control practices are important aspects of any construction project due to their ability to limit the process of erosion. Testing erosion control practices under simulated rainfall representative of conditions experienced on construction sites is important to better understand their erosion reduction capabilities. Full-scale testing using simulated rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…These were chosen deliberately based on IDF curves from countries of the Central and Eastern Africa, a region in the Sub-Saharan Africa where about 80% of the road networks are unpaved [9], [12][13][14] and thus in much need to control erosion in these roads. Using the flour method to determine the size of the raindrops [3], [7], [15][16][17], the drop sizes of 3 mm, 3.2 mm, and 3.5 mm were found, leading to the kinetic energy from the raindrops of 193.5 µJ, 244 µJ and 301.1 µJ, respectively for 30 mm/hr, 51 mm/hr and 68 mm/hr rainfall intensities. The sizes of the raindrops were satisfactory to initiate erosion of soils of 0.4 mm < D50 < 1.5 mm [18], which were found appropriate at the surface of unpaved roads [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were chosen deliberately based on IDF curves from countries of the Central and Eastern Africa, a region in the Sub-Saharan Africa where about 80% of the road networks are unpaved [9], [12][13][14] and thus in much need to control erosion in these roads. Using the flour method to determine the size of the raindrops [3], [7], [15][16][17], the drop sizes of 3 mm, 3.2 mm, and 3.5 mm were found, leading to the kinetic energy from the raindrops of 193.5 µJ, 244 µJ and 301.1 µJ, respectively for 30 mm/hr, 51 mm/hr and 68 mm/hr rainfall intensities. The sizes of the raindrops were satisfactory to initiate erosion of soils of 0.4 mm < D50 < 1.5 mm [18], which were found appropriate at the surface of unpaved roads [9].…”
Section: Methodsmentioning
confidence: 99%
“…The size of the raindrops can be determined using various methods such as the stain method, the momentum method, the immersion method, the oil method, the photographic method, and the flour method [16]. According to Horne [3] and Ricks et al [17], the stain method relates the stain on absorbent surfaces such as filter and blueprint papers to the diameter of the raindrops. Contrary, the momentum method uses both pressure transducers and piezoelectric sensors to determine the raindrops' sizes while immersion method uses collection of raindrops into an oil where they are surrounded by oil due to its low density their diameters determined using a microscope [3], [16].…”
Section: Determination Of the Raindrops' Sizementioning
confidence: 99%
“…Moreover, adding English china clay to gravelly SAND and very gravelly SAND soils improved both cohesion and plasticity indexes (Ip) which then ranged from 0% to 12%, as required for the surface soils of earth and gravel roads [20]- [22]. The raindrops fell through 2 meters above the surface of the sample and the flour method was used to determine the size of the raindrops [23]- [27]. It was found that the mean drop sizes were 3, 3.2, and 3.5 mm respectively for the 30, 51, and 68 mm/hr rainfall intensities.…”
Section: Methodsmentioning
confidence: 99%
“…Testing was performed to calibrate the simulator and conduct bare soil control tests. The researchers were able to show that rainfall intensities of the simulator conformed to ASTM D6459‐15, as did uniformity and consistency of droplet sizes (Ricks et al, 2019).…”
Section: Erosion and Sediment Controlmentioning
confidence: 99%